White Matter Connectivity in Youth at Risk for Serious Mental Illness: A Longitudinal Analysis. (30th August 2020) - Shakeel, Mohammed K; MacQueen, Glenda; Addington, Jean; Metzak, Paul D; Georgopoulos, Grace; Bray, Signe; Goldstein, Benjamin I.; MacIntosh, Bradley J; Wang, JianLi; Kennedy, Sidney H; Lebel, Catherine
Highlights: No studies investigated longitudinal white matter changes in transdiagnostic risk No significant differences in frontal white matter connectivity observed over time Changes in right anterior thalamic radiations observed before corrections Abstract: Longitudinal changes in white matter connectivity were assessed in a sample of youth at-risk for serious mental illness ( n =183; age 12-25). Diffusion tensor imaging (DTI) was acquired at baseline and 12 months from youth recruited across two sites and classified as healthy controls ( n =36), familial risk ( n =30), mild-symptoms ( n =41), attenuated syndromes ( n =70), or transition ( n =9) based on clinical assessments. Fractional anisotropy (FA) and mean diffusivity (MD) values were derived for the whole brain white matter, forceps minor, anterior cingulate, anterior thalamic radiations, inferior fronto-occipital fasciculus, superior longitudinal fasciculus, and uncinate fasciculus. MANCOVA analysis controlling for site, sex, and age showed no significant group differences in FA and MD at baseline or at 12 months. Linear mixed effects analysis showed a significant effect for time for most white matter tracts, but no effect for group, or group by time interaction. Transdiagnostic risk groups have similar profiles of WM connectivity and similar rates of change over time.